Preservation and the management of library collections - Feather, John. (London : Library Association Pub., 1996)
The preservation of information in an accessible form is the subject of this book. It is not a book about bookbinding or paper repair. It is a book about professional librarianship and library management, and it is intended for those whose professional concern is (or will be) with the effective management of the information resources which lies at the heart of every information agency. At the core of this book is a consideration of how a preservation policy is developed and managed, but technical matters cannot be ignored.
Includes index.
Includes bibliographical references: p. 159-176.
rpm 27/08/2018
Loans
Keywords: Library materials; Collection management (Libraries)